2022
DOI: 10.1002/csr.2322
|View full text |Cite
|
Sign up to set email alerts
|

The strengthening of corporate governance based on applied fuzzy logic

Abstract: Despite advances in research on corporate governance, there are still knowledge gaps. The article aims to broaden the debate on strengthening corporate governance and propose a tool to facilitate decision‐making. The research is novel because of the engagement of 117 master's students from a business school, contributing to competency‐based learning on Good Corporate Governance (GCG). This is applied research with the explanatory objective and quantitative approach through modeling and simulation. The OWA Oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Their effectiveness also responds to new societal needs, such as sustainable development [20], climate change [30], and the COVID-19 pandemic [31]. In the case of the OWA operator, it is a practical algorithm for evaluation and prioritization [32]. It is also flexible in the modeling and simulation process since it is defined by a vector of weights and not by a single parameter [32].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Their effectiveness also responds to new societal needs, such as sustainable development [20], climate change [30], and the COVID-19 pandemic [31]. In the case of the OWA operator, it is a practical algorithm for evaluation and prioritization [32]. It is also flexible in the modeling and simulation process since it is defined by a vector of weights and not by a single parameter [32].…”
Section: Introductionmentioning
confidence: 99%
“…Scientists applied the OWA operator to facilitate decision-making by public managers in sustainable transport [34]. Another study evaluated companies listed on the Lima Stock Exchange considering the level of compliance with the Principles of Good Corporate Governance [32] and in the decision-making of consumers in the city of Barcelona regarding the selection of groceries by neighborhoods that best suit their needs [35]. Finally, the literature review of this article also showed few publications of the OWA operator applied to climate change, evidencing the fifth knowledge gap and an opportunity for academic contribution.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations